Treatment efficacy of first-line immunotherapy in advanced esophageal small cell carcinoma: A real-world retrospective study - Li, Nan; Zhang, Rui xing (Frontiers in Oncology, 2025)
BackgroundSmall cell carcinoma of the esophagus (SCCE) is a rare and highly aggressive malignancy characterized by early metastatic propensity. Traditional chemotherapy has a poor curative effect and a short survival period Recent evidence demonstrates that combining immune checkpoint inhibitors (ICIs) with chemotherapy significantly improves therapeutic outcomes in both advanced esophageal carcinoma and small cell lung cancer. This study aims to evaluate the efficacy of first-line ICIs combined with chemotherapy in patients with advanced SCCE.Patients and methodsThis single-center retrospective study analyzed 31 patients with advanced SCCE who initiated first-line systemic therapy at our institution between January 2021 and August 2024. All patients received physician-determined treatment regimens. The study aimed to evaluate the efficacy of first-line immunotherapy combined with chemotherapy in advanced SCCE.ResultsMedian progression-free survival (PFS) was significantly longer in the immunotherapy group (9.3 months; 95% CI 6.3-12.3) compared to the non-immunotherapy group (5.4 months; 95% CI 3.5-7.3; P = 0.046). Patients receiving chemotherapy alone demonstrated the shortest PFS (3.2 months; 95% CI 2.1-4.3), while those receiving combined chemotherapy and immunotherapy achieved the longest PFS (10.0 months; 95% CI 3.8-16.1). Median overall survival (OS) of patients with combined immunotherapy showed a trend of prolongation (17.0 months 95% CI 12.9-21.13 vs. 11.6 months 95% CI 4.7-18.6), but no statistically significant difference was observed (p = 0.055). Multivariate analyses suggested that the combination of immunotherapy, or its absence, may affect patient prognosis. Numerical improvements were observed in the immunotherapy group for both objective response rate (ORR: 31.3% vs. 21.4%) and disease control rate (DCR: 93.7% vs. 85.7%).ConclusionEsophageal small cell carcinoma remains a highly aggressive malignancy with poor prognosis in advanced stages. This retrospective real-world study suggests that first-line immunotherapy combined with chemotherapy may significantly improve progression-free survival in patients with advanced SCCE compared to chemotherapy alone.